Tritium Air Concentration Calculation Using Passive Monitors. Issue 1 (January 2021) - Culp, Todd; Robinson, Alexandra
Abstract : Abstract: Passive tritium air monitoring was conducted at Sandia National Laboratories' Z-Machine located in New Mexico. When conducting low-level measurements, indication of the measurement's uncertainty and of the detection limit of the counting technique are important to understand. Therefore, a calculational methodology is presented to enable the determination of the airborne tritium concentration by analysis of the minimum detectible activities for the Passive Tritium Monitoring System and the laboratory counting system used. General discussions of the advantages and disadvantages of the Passive Tritium Monitoring System are provided.